Intraoperatively preventive intraperitoneal perfusion chemotherapy with lobaplatin in colorectal cancer: a prospective, randomised, controlled, multicentre study - Hao Su; Rui Zhang; Yunfeng Li; Yanke Li; Wei Pei; Zhigang Jie; Zhimin Liu; Meijin Huang; Jing Zhuang; Qian Jiang; Ming Xie; Guiying Wang; et al. (BMC Medicine)
Abstract Background Peritoneal metastasis (PM) after radical surgery is an important cause of treatment failure in colorectal cancer (CRC). Intraoperative intraperitoneal perfusion chemotherapy may be an effective method for preventing postoperative PM in patients with CRC. This study aimed to explore the safety and feasibility of intraoperatively preventive intraperitoneal perfusion chemotherapy using lobaplatin for CRC. Methods Between 12 December 2017 and 17 October 2019, 720 eligible CRC patients with T4 or N + clinical TNM stage were recruited from 25 hospitals in China. Eligible patients were randomised in a 1:1 ratio to undergo resection of CRC only (control group) or resection of CRC with intraperitoneal perfusion chemotherapy with lobaplatin intraoperatively (lobaplatin group). The primary endpoint of this trial was the rate of PM after surgery, while secondary endpoints included safety, overall survival (OS) time, recurrence-free survival (RFS) time, peritoneal recurrence-free survival (PRFS) time, and the rate of liver metastasis. Results Of 716 patients included in the full analysis set (FAS), 352 were assigned to the lobaplatin group and 364 to the control group. In the FAS population, adding intraoperatively preventive intraperitoneal perfusion chemotherapy with lobaplatin decreased the primary end point rate of 3-year PM (3.56% vs 8.75%, P = 0.0053). There was no significant difference in the 3-year OS between the groups (93.2% vs 90.4%, P = 0.1660). The 3-year RFS rate (88.1% vs 81.6%, 0.0146) and 3-year PRFS rate (96.6% vs 91.5%, P = 0.0053) were significantly higher in the lobaplatin group than the control group. There were no statistically significant differences between the two groups in the incidence (69.77% vs 64.75%) or severity of adverse events (AEs) in the safety set (SS) population. Conclusions Initiation of intraoperatively preventive intraperitoneal perfusion chemotherapy with lobaplatin reduced the 3-year PM rate in CRC patients while improving both 3-year RFS and PRFS. The treatment was well tolerated, and the safety findings were comparable with those of the control group. Trial registration Chinese Clinical Trial Registry, ChiCTR1800014617.